The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/lt.22122
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity associated with prolonged survival in liver transplant recipients

Abstract: We tested the hypothesis that religiosity (ie, seeking God's help, having faith in God, trusting in God, and trying to perceive God's will in the disease) is associated with improved survival in patients with end-stage liver disease who have undergone orthotopic liver transplantation. We studied a group of 179 candidates for liver transplantation who responded to a questionnaire on religiosity during the pretransplant psychological evaluation and underwent transplantation between 2004 and 2007. The demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
(37 reference statements)
0
9
1
Order By: Relevance
“…(28) For this reason, among confounding factors approached in this study, adherence has special importance when the study period considered includes the initial period after transplantation; during this period non-adherence poses a higher risk. (29) Adherence scale did not differ between groups. In addition, no correlation between intrinsic relation and adherence scores was seen, although scores on both scales were inversely correlated with renal function at 12 months.…”
Section: Discussionmentioning
confidence: 80%
“…(28) For this reason, among confounding factors approached in this study, adherence has special importance when the study period considered includes the initial period after transplantation; during this period non-adherence poses a higher risk. (29) Adherence scale did not differ between groups. In addition, no correlation between intrinsic relation and adherence scores was seen, although scores on both scales were inversely correlated with renal function at 12 months.…”
Section: Discussionmentioning
confidence: 80%
“…Our analyses here also pertained only to a relatively healthy general cohort. The majority of previous research on longitudinal associations between religious coping and mortality has been carried out with clinical populations (12)(13)(14)(15), and thus less is known about the dynamics of this association in nonill populations. In clinical populations it is possible that associations between religious coping and mortality might persist even after control for service attendance, but this would require further research.…”
Section: Discussionmentioning
confidence: 99%
“…In a large sample of 92,395 women aged 50-79 years from the Women's Health Initiative, positive religious coping was not associated with all-cause mortality (9). Some smaller studies likewise found little association between other measures of religious participation and mortality (12,13), but the literature is somewhat mixed, and some small studies show that religious coping is associated with lower mortality among clinical populations (14,15). It is possible that lack of definitive results in the literature on the associations between other measures of R/S and all-cause mortality are due to a lack of large prospective cohort studies with which to examine these associations, with a few exceptions noted above.…”
mentioning
confidence: 99%
“…The positive results of Spiritual religious coping have already been described in relation to pain, physical weakness, heart diseases, infectious diseases and cancer (3) , as well as in relation to hepatitis C (4) and liver transplant patients (5) .…”
Section: Rev Esc Enferm Uspmentioning
confidence: 94%